What is a Spiritual Education? - Ward, Graham (The way, 2025)
The article explores the nature of spiritual education, emphasizing the connection between human spirit and divine Spirit through personal reflection, poetry and the act of singing as a form of prayer and expression. It highlights how personhood, derived from the Latin persona ("to sound through"), involves the integration of body (soma), mind (psuchê), and spirit (pneuma) in continual growth, and engagement with the world, ultimately participating in the redemption of creation through Christ.